DETERMINANTS OF PROFITABILITY OF SHARIA REGIONAL DEVELOPMENT BANKS IN INDONESIA 2014-2017 - Kuni Farikhah; Lina Nugraha Rani (Universitas Negeri Surabaya, 2019)
This study aims to determine the effect of Third Party Funds, Financing to Deposit Ratio (FDR), Profit Sharing and Non-Performing Financing (NPF) on the profitability of Sharia BPDs in Indonesia in 2014-2017. Measurement of profitability uses the Return on Asset (ROA) ratio . The data used is obtained through the financial statements of the Regional Development Bank (BPD) Sharia known as the Islamic Development Bank. This research method uses a quantitative approach using panel data regression analysis techniques using EViews 10.0 software. The results of statistical tests show that the variables of Third Party Funds and Non Performing Financing (NPF) have a negative and significant effect on the profitability of the Syariah BPD. While the Financing to Deposit Ratio (FDR) and Profit Sharing Financing variables have no significant effect on the profitability of the Sharia BPD.